2012
DOI: 10.1111/j.1348-0421.2011.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pseudomonas aeruginosa isolates from dogs and cats in Japan: current status of antimicrobial resistance and prevailing resistance mechanisms

Abstract: Seventy-three Pseudomonas aeruginosa isolates were collected from dogs and cats in Japan to investigate antimicrobial susceptibility and resistance mechanisms to anti-pseudomonal agents. Resistance rates against orbifloxacin, enrofloxacin, ciprofloxacin, cefotaxime, aztreonam and gentamicin were 34.2, 31.5, 20.5, 17.8, 12.3 and 4.1%, respectively. The degree of resistance to cefotaxime, orbifloxacin, and enrofloxacin was greatly affected by efflux pump inhibitors, indicating overexpression of efflux pump contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
38
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 21 publications
(39 reference statements)
14
38
1
2
Order By: Relevance
“…Overall, the rates of antibiotic resistance were low. Similar results were reported in a previous Japanese study (6) and confirmed in other countries (12,13).…”
supporting
confidence: 93%
“…Overall, the rates of antibiotic resistance were low. Similar results were reported in a previous Japanese study (6) and confirmed in other countries (12,13).…”
supporting
confidence: 93%
“…Besides the difference in the methods used, there is a difference between the origins of the isolates. Isolates included in the study from 2011 were all collected from the ears of dogs with otitis externa, and it is well known that otic isolates tend to show higher resistance rates to several antimicrobials, including enrofloxacin and other fluoroquinolones (PETERSEN et al, 2002;WILDERMUTH et al, 2007;HARADA et al, 2012). Nevertheless, the sensitivity rate to enrofloxacin found in this study was still lower than sensitivity rates observed in other studies, where susceptibility ranged between 16% and 51% (COLOMBINI et al, 2000;MARTIN BARRASA et al, 2000;McKAY et al, 2007;WERCKENTHIN et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
“…This finding indicates that carbapenemases are uncommon among Enterobacter spp. isolates from companion animals in Japan, as well as among other Gram-negative bacteria [31,32,40,41], although they have been reported among animal isolates in other countries [12] and among human isolates in Japan [42]. …”
Section: Discussionmentioning
confidence: 99%